Morphology and molecular phylogeny of Umbraulva spp. (Ulvales, Ulvophyceae), and proposal of Ryuguphycus gen. nov. and R. kuaweuweu comb. nov. Issue 1 (2nd January 2021) - Kawai, Hiroshi; Hanyuda, Takeaki; Mine, Ichiro; Takaichi, Shinichi; Terada, Ryuta; Kitayama, Taiju
ABSTRACT: The reproductive structures, early development and carotenoid composition of Umbraulva kuaweuweu, which is a deep-water ulvacean species recently reported from Hawaii, are reported for the first time using the specimens collected by dredging at 30 m depth from Ogasawara Islands and Mageshima in southern Japan. Although Umbraulva kuaweuweu had siphonaxanthin as in U. japonica, a characteristic carotenoid of Umbraulva, U. kuaweuweu lacked α-carotene and β-carotene. U. kuaweuweu differed markedly from U. japonica in thallus morphology and reproductive structures: cell shape, presence/absence of inner rhizoidal filaments in the upper parts of thalli, solid/partly saccate thalli, and developmental processes of zoids. Multigene concatenated DNA sequences of chloroplast rbc L and tuf A genes, and nuclear 18S, 5.8S, 28S rDNA and rDNA ITS1 and ITS2 regions indicated separation of U. kuaweuweu from the clade comprised of the generitype U. japonica, U. amamiensis, U. dangeardii and U. kaloakulau . In conclusion, based on the distinctive morphology, life history, carotenoid composition and molecular phylogeny, we propose the establishment of a new genus Ryuguphycus gen. nov. to accommodate U. kuaweuweu, as R. kuaweuweu comb. nov.